2015
DOI: 10.1159/000381991
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Lipids with Outcomes in Hispanic Hemodialysis Patients of the West versus East Coasts of the United States

Abstract: Background: Paradoxical associations exist between serum lipid levels and mortality in patients on maintenance hemodialysis (MHD) including those of Hispanic origin. However, there are significant racial and ethnic variations in patients of ‘Hispanic' background. We hypothesized that clinically meaningful differences existed in the association between lipids and survival in Hispanic MHD patients on the West versus East Coast. Methods: We examined the survival impact of serum lipids in a 2-year cohort of 15,109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…31,32 These findings may partly explain the association of elevated HDL-C levels with worse outcomes in some subgroups of patients with chronic kidney disease/ hemodialysis. [15][16][17] In addition, recently, we reported that higher serum concentrations of triglycerides are paradoxically associated with decreased risk of cardiovascular and all-cause mortality in patients undergoing hemodialysis. 14 In light of these findings, it is not surprising that, in the current study, we find a graded inverse association between serum levels of non-HDL-C, which include the major triglyceride-rich lipoproteins, and mortality in patients undergoing incident hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 These findings may partly explain the association of elevated HDL-C levels with worse outcomes in some subgroups of patients with chronic kidney disease/ hemodialysis. [15][16][17] In addition, recently, we reported that higher serum concentrations of triglycerides are paradoxically associated with decreased risk of cardiovascular and all-cause mortality in patients undergoing hemodialysis. 14 In light of these findings, it is not surprising that, in the current study, we find a graded inverse association between serum levels of non-HDL-C, which include the major triglyceride-rich lipoproteins, and mortality in patients undergoing incident hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, several studies have found that higher serum HDL cholesterol levels are associated with worse survival in patients with chronic kidney disease and those undergoing hemodialysis. [15][16][17] However, the relationship between serum non-HDL-C level and outcomes is less clear, given that most of the data available are based on small prospective studies with a limited number of patients and major limitations. 18,19 Meanwhile, the largest observational cohort study conducted in 45 390 patients undergoing prevalent hemodialysis showed a positive association between elevated serum non-HDL-C levels and higher rates of incident myocardial and cerebral infarction; however, these findings were not associated with an increased risk of mortality.…”
mentioning
confidence: 99%
“…However, genetic, ethnic, and racial factors, as well as the HD treatment and the ultrafiltration rate, can affect serum lipids and therefore patients' outcomes. 19,20 Predialysis serum creatinine concentration has been suggested as an indirect measure of muscle mass in HD patients and the International Society of Renal Nutrition and Metabolism (ISRNM) includes this parameter in the diagnostic criteria for PEW. In our study, we observed lower serum creatinine and CI in the group of patients with BCMI <6.4 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This important point is also relevant when evaluating African American or Hispanic HD patients of different ancestry. For instance, among African American patients, the frequency of apolipoprotein L1 (APOL1) genetic variants, which can be related to the place of origin in their African ancestry, can have an impact on progression of 15 found differences in the association of serum lipid levels with outcomes in HD patients of Hispanic origin depending on whether they resided on the West or East Coast of the US. These differences may be reflective of the fact that patients classified as Hispanic on the East Coast have more individuals of Afro Caribbean ancestry, whereas those on the West Coast are more likely to be Mexican American.…”
Section: Impact Of Race and Ethnicity On The Obesity Paradoxmentioning
confidence: 99%